2018
DOI: 10.5489/cuaj.5468
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative pad usage is independently associated with failure of non-adjustable male trans-obturator slings in otherwise well-selected patients

Abstract: Introduction: Our objective was to determine which clinical factors are associated with failure to achieve continence after nonadjustable trans-obturator sling in otherwise well-selected men undergoing treatment for post-prostatectomy incontinence (PPI). Methods: A retrospective review of AdVance/AdVanceTM XP male sling procedures was performed from December 2006 to May 2017. Patients with known risk factors for sling failure, including severe incontinence (>5 pads), radiation therapy, or detrusor dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A study comparing patients treated with either the AdVance sling or the AdVance XP sling revealed a total cure rate of 77% following a median follow-up of 49 months [20, 29]. From a patient’s point of view, the AdVance XP sling shows undeniable advantages such as no mechanical components and the ability to function without relying on patient-related cognition [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing patients treated with either the AdVance sling or the AdVance XP sling revealed a total cure rate of 77% following a median follow-up of 49 months [20, 29]. From a patient’s point of view, the AdVance XP sling shows undeniable advantages such as no mechanical components and the ability to function without relying on patient-related cognition [14].…”
Section: Discussionmentioning
confidence: 99%
“…Rehder et al [33] described a long-term follow-up of the AdVance sling after 36 months, showing cure rates of 53.0% in total, including a cured and improved rate of 76.8% (patients defined as cured using 0–1 pads/24 h). Zemp et al [14] were able to show continence rates of 82.3% in patients with no identified risk factors for AdVance sling failure, described in a mean follow-up of 43 months. Consistent with the findings of Zuckerman et al [31] stating a cure rate of 62% of patients either described as cured or improved after a median follow-up of 36 months, their findings indicated declining functional rates over the described follow-up time [11].…”
Section: Discussionmentioning
confidence: 99%
“…Cure as defined by 0 PPD was achieved by 50% of ideal patients versus only 22% of nonideal patients (68). Other studies have also found degree of preoperative incontinence to be highly predictive of sling success (16,21,69). One should be aware that the definition of incontinence has been debated by many.…”
Section: Work-up/identification Of the Ideal Sling Candidatementioning
confidence: 98%
“…Risk factors for failed continence following sling placement include weak residual urethral sphincter function, poor sphincter coaptation, no tunneling of the sling, low bladder capacity, and number of preoperative pads used. [5][6][7] Anecdotally, All patients who underwent AdVance male urethral sling placement between January 2013 and January 2019 at a single institution by two surgeons (MJM, TAG) were identified for inclusion in the study. Preoperative, intra-operative, and postoperative variables were collected using retrospective chart review.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for failed continence following sling placement include weak residual urethral sphincter function, poor sphincter coaptation, no tunneling of the sling, low bladder capacity, and number of preoperative pads used. 57 Anecdotally, men with obesity are considered more challenging surgically for placement of a retrourethral sling because of body habitus challenges associated with passing the trocar, however, there are few studies examining the impact of obesity on male sling surgery or outcomes. 8,9 The aim of this study was to evaluate the impact of obesity on AdVance male urethral sling placement, focusing on operative time as a surrogate for surgical complexity and need for pads postoperatively.…”
Section: Introductionmentioning
confidence: 99%